DETERMİNATİON OF WORKİNG CONDİTİONS OF THE WORKERS EMPLOYED İN THE ÇANKIRI SMALL SCALE INDUSTRİAL ESTATE (Third Sector Social Economic Review, 2011)
This research was planned and carried out for the purpose of determining the working conditions of workers employed in the Çankırı Small Scale Industrial Estate. The data were collected from 167 workers from different workplaces by means of a questionnaire. The percentage of male workers is 89.8 % and female workers is 10.2 %. Average age of the participants is 21.51±8.25. It has been determined that 58.1 % of the workers faced various occupational accidents in the previous year.When the conditions in the working places were examined; it was identified that 46.7 % of the working places did not have local illumination, the illumination in 85.0 % of them caused eyes of the workers to be dazzled, 58.1 % of them did not have heating or cooling systems, 37.1 % of them did not have enough number of windows for ventilation, 37.1 % of them had toxic steam, explosive gas etc.@in the environment, 44.3 % of them had noise levelsthat prevented communication, 35.3 % of them had noise that was continually at the same level. When asked about the precautions taken against the inappropriatenesses in the working environment; 33.5 % of the workers stated that they did not have breaks after tiring working sessions or in a regularbasis, 44.9 % of them stated that there was not suitable resting places to be used in the breaks, 58.1 % of them stated that necessary precautions against toxic materials, gases, dust and smoke that present in the environment were not taken, 64.7 % of them stated that they did not have regular medical check-ups.
Keywords: Worker; workplace; working conditions